2019
DOI: 10.3390/app9030468
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Calcium Alginate Capsules for Self-Healing Asphalt

Abstract: It has been demonstrated that calcium alginate capsules can be used as an asphalt healing system by pre-placing rejuvenator (healing agent) into the asphalt mix and releasing the rejuvenator on demand (upon cracking). This healing mechanism relies on the properties of capsules which are determined by the capsule preparation process. In this study, to optimize the calcium alginate capsules, capsules are prepared using varying Alginate/Rejuvenator (A/R) ratios. Light microscope microscopy and Environmental Scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Overall, the encapsulation of each oil rejuvenator resulted in capsules with homogeneous size as evidenced their low coefficient of variation (CV) in the histograms. Additionally, representative SEM images taken from the cross-sectional area of both biocapsules (Figure 5d-f) reveals that the rejuvenators were encapsulated in an internal polynuclear microstructure, also reported by Zhang et al [22] and Xu et al [23]. They hypothesise that a polynuclear internal microstructure can provide: (1) a controlled liberation of the rejuvenating agent, providing multiple healings on aged bitumen, and (2) good thermal and mechanical stability.…”
Section: Results and Discussion Influence Of The Rejuvenating Agents supporting
confidence: 76%
See 1 more Smart Citation
“…Overall, the encapsulation of each oil rejuvenator resulted in capsules with homogeneous size as evidenced their low coefficient of variation (CV) in the histograms. Additionally, representative SEM images taken from the cross-sectional area of both biocapsules (Figure 5d-f) reveals that the rejuvenators were encapsulated in an internal polynuclear microstructure, also reported by Zhang et al [22] and Xu et al [23]. They hypothesise that a polynuclear internal microstructure can provide: (1) a controlled liberation of the rejuvenating agent, providing multiple healings on aged bitumen, and (2) good thermal and mechanical stability.…”
Section: Results and Discussion Influence Of The Rejuvenating Agents supporting
confidence: 76%
“…Nonetheless, for a successful incorporation of encapsulated rejuvenators into asphalt pavements, the biocapsules should meet a series of specifications related to the manufacturing of asphalt mixtures. From a thermal point of view, capsules should resist the temperature of fabrication of HMA around 160° C, as stated by Xu et al [23]. While, from a mechanical point of view, Yamaç et al [25] stated that capsules should at least resist a compressive strength value of 10 N to prevent breaking during mixing and compaction.…”
Section: Morphological and Physical Properties Of The Biocapsulesmentioning
confidence: 99%
“…The calcium alginate capsules and the steel fibres were used to build the self-healing systems in PA. The calcium alginate capsules used in this study were prepared in Microlab, TUDelft, Delft, the Netherlands and the microscopic images in Figure 4 show that the capsules had a diameter of 1.95 mm and a honeycomb-like structure [ 24 , 26 ]. Aiming to improve the conductivity of PA to achieve induction healing, steel fibres were used in the induction healing system and combined healing system.…”
Section: Methodsmentioning
confidence: 99%
“…The authors of an earlier study [ 24 , 25 ] have investigated the calcium alginate capsules healing system, which is illustrated in Figure 2 . The calcium alginate capsules encapsulating the rejuvenator were prepared and optimized, and their crack healing effect was demonstrated in bituminous materials [ 24 , 26 ]. It was also found that the healing efficiency of the induction heating technique could be largely reduced by asphalt ageing and gradient healing [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [7] studied induction heating-assisted compaction of pavement structure, which appeared to be an effective way to improve mix compaction and compatibility at low temperature. Xu et al [8] applied calcium alginate microcapsules encapsulating an asphalt bitumen rejuvenator to improve the self-healing of bitumen once a crack initiates in the asphalt mixture. Wang et al [9] studied the nano-TiO2 photocatalytic coating on the surface of pavement, which endows the pavement with air-purifying and self-cleaning abilities.…”
mentioning
confidence: 99%